GAYA KOMUNIKASI INTERPERSONAL USTADZ DI PONDOK PESANTREN AR-RISALAH MLANGI DALAM PROSES PEMBENTUKAN KARAKTER SANTRI - Meti Ayu Wulandari; Kholifatul Fauziah (Nusantara Hasana Journal, 2023)
Interpersonal communication style has an important role in the formation of the character of students. The purpose of this research is to describe the ustadz's interpersonal communication style towards students in character building at the Ar-Risalah Mlangi Islamic Boarding School and identify the factors that influence it. This research is a qualitative descriptive study by taking the research location at the Ar-Risalah Mlangi Islamic Boarding School, Yogyakarta. The process of collecting data was carried out through observation, interviews, and documentation. The results of this study indicate that the equalitarian style is the most dominant communication style used by ustadz in character building. This is because ustadz can build a relaxed and comfortable atmosphere and have a two-way flow of communication and produce good feedback or responses from students. Supporting factors that influence the process of character formation is by carrying out prayer attendance as well as teaching and learning activities.